The Relationship between High Glycemic Index Food Consumption and Blood Sugar Levels of Type II Diabetes Mellitus Patients at the Baiturrahman Health Center, Banda Aceh City - Silvia Wagustina; Eva Fitriyaningsih; Rosi Novita (PT Yapindo Jaya Abadi, 2026)
Type II diabetes mellitus (DM) is a metabolic disorder characterized by insulin resistance and/or decreased insulin secretion that causes an increase in blood glucose levels. Consumption of foods with a high glycemic index is known to contribute to increased blood sugar levels. This study aims to analyze the relationship between the consumption of foods with a high glycemic index and blood sugar levels in type II DM patients in the working area of the Baiturrahman Health Center, Banda Aceh City. This study uses an analytical descriptive design with a cross-sectional approach which was carried out in January–November 2024, with a sample of 42 respondents. Food consumption data was obtained through the 3×24-hour food recall method, while blood sugar levels were measured using a glucometer by health workers. Data analysis was carried out using the Chi-Square test. The results showed that most patients who ate foods with a low glycemic index had normal blood sugar levels (94.2%), while patients who ate foods with a high glycemic index tended to have high blood sugar levels (76%). The results of the statistical test showed a value of p = 0.003 (p < 0.05), which means that there is a statistically significant relationship between the consumption of foods with a high glycemic index and blood sugar levels in patients with type II DM. It was concluded that the consumption of foods with a high glycemic index was significantly related to an increase in blood sugar levels at the time. Therefore, glycemic index-based dietary arrangements are important in the control of type II DM.